Disasters in the Perspective of Disaster Sociology - Suhaeb, Firdaus W.; Kaseng, Ernawati S. (PINISI Discretion Review, 2024)
Paradigm changes occur over time, especially earthquakes and tsunamis in Indonesia. This paradigm transformation is also influenced by changes in people's views that have shifted from conventional to holistic. Thus, this study aims to describe the paradigm determinants and theories of disaster sociology. The study of this article uses the literature study method, Data types, namely using secondary data, such as library materials. Problem data analysis is analyzed according to the research problem. Then the results of the research are compiled, analyzed, and drawn conclusions. This research study shows that disaster management involves concepts, conclusions and analysis from various disciplines, including sociology. Understanding the patterns of individual or community knowledge about disaster threats and how they deal with them is very important in disaster planning and preparedness activities. Sociological perspectives, both paradigms and theories, are not just knowledge, but guidelines in designing programs, setting priorities, and developing sustainable disaster management implementation strategies are a must. Proper implementation and strategy are effective responses and build sustainable preparedness in dealing with potential disaster risks.